2008
DOI: 10.1111/j.1360-0443.2007.02064.x
|View full text |Cite
|
Sign up to set email alerts
|

The natural course of cannabis use, abuse and dependence during the first decades of life

Abstract: Among youth who have used cannabis repeatedly (five times or more) cannabis use is fairly stable and rates of remission relatively low until age 34 years. Patterns of progression suggest that early targeted preventive measures should delay first use and reduce the number of experiences using cannabis, as these factors appear critical in progression to persistent cannabis use and cannabis dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
131
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 163 publications
(147 citation statements)
references
References 25 publications
9
131
2
2
Order By: Relevance
“…As expected, both cannabis use and depressive symptoms were modestly stable from ages 17 to 22, consistent with findings from previous research on adolescent males transitioning into adulthood (Hankin et al, 1998;Perkonigg et al, 2008). Paradoxically, within the cannabis-user and milddepression subsamples, less consistent stability was evident for cannabis use and depressive symptoms, respectively, which may be accounted for by regression to the mean, as those with above-average cannabis use and depression scores would be expected to show decreases relative to the rest of the sample (Nielsen et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
“…As expected, both cannabis use and depressive symptoms were modestly stable from ages 17 to 22, consistent with findings from previous research on adolescent males transitioning into adulthood (Hankin et al, 1998;Perkonigg et al, 2008). Paradoxically, within the cannabis-user and milddepression subsamples, less consistent stability was evident for cannabis use and depressive symptoms, respectively, which may be accounted for by regression to the mean, as those with above-average cannabis use and depression scores would be expected to show decreases relative to the rest of the sample (Nielsen et al, 2007).…”
Section: Discussionsupporting
confidence: 79%
“…On the other hand, using five times or more as a cut-off for lifetime use is likely to select out most of the users who have experimented with cannabis without proceeding into continued use. This is illustrated by Perkonigg et al (2008), who refer to the use of cannabis of five times or more as ' repeated use '. Their study on the long-term natural course of cannabis use in a community sample of adolescents revealed that these repeated users were almost three times more likely to report cannabis use at 10-year follow-up (odds ratio 2.8, 95 % confidence interval 1.6-4.7) compared with those who had used cannabis fewer than five times.…”
Section: Discussionmentioning
confidence: 99%
“…With notable exceptions (Merline et al, 2004;Patton et al, 2007), past studies which report on the relationship between socioeconomic position and substance use studied one substance at a time (Fagan et al, 2005;Perkonigg et al, 2008;Schulenberg et al, 1996;Schulenberg et al, 2005;Swift et al, 2008) or overall symptoms of abuse (Barrett and Turner, 2006), making it difficult to make cross-substance comparisons.…”
Section: Introductionmentioning
confidence: 99%
“…To date research in this area was limited to the United States (Merline et al, 2004;Windle et al, 2005;Windle and Wiesner, 2004), Australia/New Zealand (Swift et al, 2008), and Northern Europe (Netherlands, Germany) (Karam et al, 2007;Perkonigg et al, 2008), and few studies were able to account for pre-existing individual and family characteristics which may determine both socioeconomic position and substance abuse in young adulthood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation